Investigation on Mechanical and Microstructure Properties of Steel Fiber Reinforced Concrete - Qinyuan Zhang; Wenwen Xu; Yichen Sun; Yongcheng Ji (Advances in Materials Science and Engineering)
This paper studied the microscopic and mechanical property degradation of axially compressed concrete with different steel fiber content under chemical erosion and freeze-thaw environment. Concrete cylinders with three types of steel fiber contents (0%, 1%, 2%) were selected to study the durability behavior concerning different environmental effects up to 28 days, which included tap water, 3.5% sodium chloride solution, 10% sodium sulfate solution, 5% sulfuric acid solution, 2 mol/L sodium hydroxide solution, and 100 freeze-thaw cycles. The variation of specimens’ microstructure and axial bearing capacity with different fiber content was studied with the chemical erosion cycle increase, and the mass and pH variations of the specimen were measured. According to the law of micro-cracks, the deterioration degree was judged, and a numerical analysis model was established to quantify the reliability of the structure with different fiber content. The results show that the addition of steel fiber can effectively improve the axial bearing capacity of concrete, and a freeze-thaw environment and chemical erosion can accelerate fiber-reinforced concrete’s failure. The optimal content of steel fiber was determined, which is 1% for sodium chloride and sodium sulfate environments, and 2% for the freeze-thaw cycle, dilute sulfuric acid, and sodium hydroxide environments. The finite element software Abaqus was used to simulate and analyze the freeze-thaw cycle and mechanical test of concrete, which verified the rationality of the test results. Research results will provide a theoretical basis for predicting the performance deterioration of steel fiber reinforced concrete under different erosion conditions and periods.